Usability and user friendliness estimation of business german course on moodle platform - Zaitseva, Natalia; Зайцева, Наталя Володимирівна; Зайцева, Наталья Владимировна (My University, 2016)
The research is devoted to estimation of usability and user friendliness of Business German course on Moodle platform on basis of questionnaire among engineering Master’s program students.
Keywords: e-Learning platform; user friendliness; distance learning course materials; Business German course